Desilication of small crystal ZSM-5 and its preparation method

By employing ZSM-5 zeolites with specific MFI backbone characteristics and desilication using suitable bases, the challenge of enhancing mesopority with minimal silica loss is addressed, resulting in improved catalytic performance and reduced costs.

JP2025509589APending Publication Date: 2025-04-11ECOVYST CATALYST TECHNOLOGIES LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024554826
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-15
Filing Date
2023-03-15
Publication Date
2025-04-11

Smart Images

  • Figure 2025509589000001
    Figure 2025509589000001
  • Figure 2025509589000002
    Figure 2025509589000002
  • Figure 2025509589000003
    Figure 2025509589000003
Patent Text Reader

Abstract

A desilicate crystalline material is disclosed that has a MFI (ZSM-5) framework type, a silica to alumina molar ratio (SAR) of 15 or greater, and an average crystallite size of about 200 nm or less. The disclosed crystalline material has a crystallite size of at least 0.40 cm 3 / g mesopore volume and at least 0.10 cm 3 / g micropore volume. A method for producing the desilicate crystalline material is also disclosed. The method includes mixing a starting ZSM-5 material having an average crystal size of 200 nm or less in a base solution, recovering the solids by filtration or other separation methods, drying, and optionally calcining the solids.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (Priority) This application claims priority to U.S. Provisional Patent Application No. 63 / 319,921, filed March 15, 2022, which is incorporated by reference in its entirety herein.

[0002] The present disclosure relates generally to ZSM-5 zeolites having improved mesoporosity. The present disclosure also relates to a method for producing ZSM-5 by desilication of small crystallite ZSM-5 zeolites. [Background technology]

[0003] Mesoporous zeolites are a type of zeolite that has a high mesopore volume (as opposed to traditional zeolites that have low or no mesoporosity) and are well known for their improved diffusion properties. Faster diffusion in the mesopores allows better access of reactants to the catalytic sites within the micropores of the zeolite, resulting in improved catalytic performance.

[0004] There are various ways to increase the mesoporosity of zeolites. One method is the use of mesoporogens during zeolite synthesis. Mesoporogens are typically organic compounds that form and fill mesopores during zeolite synthesis. Another method is the synthesis of nano-sized zeolites with short diffusion distances within the individual crystals and intercrystalline mesoporosity. Yet another method is the selective removal of parts of the zeolite framework, where the voids formed are in the mesopore size range. The selective removal of the zeolite framework is usually achieved by the process of zeolite desilication using a suitable base. Part of the zeolite framework dissolves during the desilication process, which can lead to loss of material and therefore increased production costs.

[0005] Each of these methods has inherent limitations in terms of cost and final mesopore structure, therefore there is a need for suitable zeolite materials that can provide improved mesoporosity at the expense of minimizing material loss during the desilication process.

[0006] ZSM-5 zeolites (MFI frameworks defined by IZA) are used in industry for many petrochemical applications. ZSM-5 zeolites can be synthesized with or without organic structure directing agents (OSDAs) such as tetrapropylammonium bromide. ZSM-5 zeolites with improved mesoporosity, produced with minimal losses during desilication, can be advantageous materials for such applications.

[0007] Thus, there is a need to develop ZSM-5 zeolites that can be desilicate to increase mesoporosity in an economical manner, such as achieving maximum mesoporosity at the expense of minimizing material loss during desilication. The disclosed ZSM-5 zeolites and methods for making same are directed to overcoming one or more of the above problems and / or other problems of the prior art. Summary of the Invention

[0008] To address the aforementioned needs, materials are disclosed having an MFI framework type (ZSM-5) that can be desilicate to form a higher mesopore volume per unit weight of silica loss compared to previously available materials having an MFI framework and a silica to alumina ratio (SAR; ratio of silica to alumina) similar to the parent form.

[0009] In one embodiment, a parent ZSM-5 zeolite is selected having an SAR range of 15 or greater, an average crystal size of 200 nm or less. The zeolite may be in the as-synthesized form (including OSDA), a calcined alkali-containing form, an ammonium form, or a proton form, none of which have been previously subjected to desilication.

[0010] In another embodiment, the mesoporosity of ZSM-5 zeolite is increased by desilication of the parent zeolite, which may be carried out using a suitable base such as sodium hydroxide or potassium hydroxide with or without the presence of a quaternary ammonium compound in the form of a salt or hydroxide.

[0011] In another embodiment, the desilication step is carried out in the presence of 1-20 mmol of base per gram of anhydrous zeolite, at a temperature between 0° C. and 100° C. for 0.5-24 hours, at a solids content of 1-30% by weight, and optionally in the presence of 0.1-10 mmol of a quaternary ammonium compound in the form of a salt or hydroxide per gram of anhydrous zeolite.

[0012] In another embodiment, the desilicate form of the zeolite is subjected to ion exchange with an ammonium salt, such as ammonium nitrate or ammonium chloride, optionally in combination with an acid, such as nitric acid or hydrochloric acid.

[0013] In another embodiment, the desilicate and ion-exchanged form of the ZSM-5 zeolite has a ΔV / silica loss of at least 0.8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] (definition) "Micropore Volume" or "V micro " is used to indicate the total volume of pores with a diameter of less than 20 Angstroms. "Initial micropore volume" means the micropore volume of the freshly prepared crystalline material before exposure to desilication conditions. The evaluation of the micropore volume is obtained from the BET measurement technique, in particular by an evaluation method called the t-plot method (or sometimes simply the t-law), as described in the literature (Journal of Catalysis 3, 32 (1964)).

[0015] Here, "mesopore volume" or "mesoporosity" or "V meso" is the volume of pores with diameters greater than 20 Å and less than or equal to 600 Å, calculated by applying the BJH method to the desorption branch of the N2 isotherm.

[0016] As used herein, "parent zeolite" or "parent material" refers to the initial zeolite material for desilication before it is exposed to desilication conditions.

[0017] "Defined by the Structure Committee of the International Zeolite Association (IZA)" means, without limitation, structures set out in Baerlocher et al. "Atlas of Zeolite Framework Types," Sixth Revised Edition (Elsevier 2007), which is incorporated herein by reference in its entirety.

[0018] Silica loss is calculated according to the following formula: Silica loss = 1-SAR d / SAR p (In the formula, SAR d is the SAR in alkaline or ammonium form after desilication, and SAR p is the SAR of the undesilicate parent zeolite, where silica loss is expressed as a percentage.

[0019] ΔV is calculated between the difference in mesopore volume of the ammonium exchanged desilicate zeolite and the mesopore volume of the ammonium exchanged non-desilicate zeolite (parent material) and is expressed in cc / g.

[0020] ΔV / silica loss is calculated as the ratio of ΔV to silica loss and represents the increase in mesopore volume per percentage of silica loss.

[0021] "Average crystal size" is the average size of the zeolite crystals along the longest crystal dimension, averaged over 100 crystals randomly selected from an SEM micrograph.

[0022] A "small crystallite ZSM-5 zeolite" is defined as a ZSM-5 material having an average crystallite size of about 200 nm or less, e.g., 150 nm or less, 100 nm or less, 50 nm or less, or even 40 nm or less. In various embodiments, the small crystallite ZSM-5 zeolite has an average crystallite size in the range of 40-200 nm, e.g., 40-150 nm, or even 50-100 nm.

[0023] Applicants have surprisingly discovered that by selecting a zeolite with an MFI framework having certain parameters, such materials can be advantageously used to desilicate with higher efficiency (higher ΔV / silica loss) than conventional commercial zeolites with an MFI framework.

[0024] In a first embodiment, a ZSM-5 zeolite is described, where the zeolite has an SAR of 15 or greater and an average crystal size of 200 nm or less. The zeolite may be in the as-synthesized form (containing OSDA), the calcined alkali-containing form, the ammonium form, or the proton form, none of which have been previously subjected to desilication.

[0025] Applicants have also surprisingly discovered that the presence of an OSDA in the parent zeolite can be advantageously used to desilicate such materials with even greater efficiency (higher ΔV / silica loss) than conventional commercial zeolites having an MFI framework or the zeolites of the present invention having an MFI framework in a calcined OSDA-free form.

[0026] In another embodiment, the mesoporosity of ZSM-5 zeolite is increased by desilication of the zeolite. Desilication can be carried out using a suitable base such as sodium hydroxide or potassium hydroxide. The mixture of zeolite and base solution is defined as a desilication suspension or slurry. Optionally, a quaternary ammonium compound in the form of a salt or hydroxide may be added to the desilication slurry.

[0027] In another embodiment, the desilication step is carried out using 1-20 mmol of base per gram of anhydrous zeolite. The temperature of the desilication step may range from 0° C. to 100° C. The total time of the desilication may range from 0.5 to 24 hours. The solids content, defined as the weight percentage of anhydrous zeolite relative to the total weight of the desilication slurry, may range from 1 to 40 wt.%.

[0028] In another embodiment, at least one quaternary ammonium compound in the form of a salt or hydroxide may optionally be added to the desilication slurry in the range of 0.1 to 10 mmol / g of quaternary ammonium compound per gram of anhydrous zeolite.

[0029] In another embodiment, the desilicate form of the zeolite is subjected to ion exchange to remove alkali cations from the zeolite, typically with ammonium salts such as ammonium nitrate or ammonium chloride.

[0030] In another embodiment, an acid such as nitric acid or hydrochloric acid may be used in addition to the ammonium salt during ion exchange to facilitate dealkalization of the desilicate mesoporous zeolite. The ion exchange is carried out using 1-50 mmol of ammonium salt and, optionally, 1-20 mmol of acid per gram of anhydrous zeolite. The temperature of the ion exchange step may range from 20° C. to 100° C. The total time of the ion exchange may range from 0.5 to 24 hours. The ion exchange may be repeated to achieve the desired residual amount of alkali in the zeolite.

[0031] In another embodiment, the desilicate and ion-exchanged form of the ZSM-5 zeolite has a ΔV / silica loss of at least 0.8. EXAMPLES

[0032] The following non-limiting examples, which are intended to be illustrative, further clarify the present disclosure.

[0033] Example 1 50 g of calcined OSDA-free ZSM-5 zeolite of SAR51 having an average SEM crystal size of 50 nm as shown in Table 1 was added to 238 g of DI water (deionized water) and mixed at room temperature. 29 g of 50 wt % sodium hydroxide solution was added to the zeolite suspension in water and the resulting mixture was stirred at room temperature for 2 hours. The desilicate zeolite was then filtered and washed with DI water.

[0034] Ammonium exchange of the desilicate zeolite was carried out using two contacts with ammonium nitrate solution (ammonium nitrate / zeolite weight ratio 2.5) at 80° C. for 2 hours. After each contact, the zeolite was filtered and washed with DI water. The ammonium exchanged sample was dried in air at 105° C. The ammonium exchanged sample exhibited the properties summarized in Table 1.

[0035] Example 2 50 g of the same starting material as in Example 1 was added to 229 g of DI water and mixed at room temperature. 38 g of 50 wt % sodium hydroxide solution was added to the zeolite suspension in water and the resulting mixture was stirred at room temperature for 2 hours. The desilicate zeolite was then filtered and washed with DI water.

[0036] Ammonium exchange of the desilicate zeolite was carried out using two contacts with ammonium nitrate solution (ammonium nitrate / zeolite weight ratio 2.5) at 80° C. for 2 hours. After each contact, the zeolite was filtered and washed with DI water. The ammonium exchanged sample was dried in air at 105° C. The ammonium exchanged sample exhibited the properties summarized in Table 1.

[0037] Example 3 50 g of the same starting material as in Example 1 was added to 257 g of DI water and heated to 40° C. 9.5 g of 50 wt % sodium hydroxide solution was added to the zeolite suspension in water and the resulting mixture was stirred for 2 hours at 40° C. The desilicate zeolite was then filtered and washed with DI water.

[0038] Ammonium exchange of the desilicate zeolite was carried out using two contacts with ammonium nitrate solution (ammonium nitrate / zeolite weight ratio 2.5) at 80° C. for 2 hours. After each contact, the zeolite was filtered and washed with DI water. The ammonium exchanged sample was dried in air at 105° C. The ammonium exchanged sample exhibited the properties summarized in Table 1.

[0039] Example 4 50 g of the same starting material as in Example 1 was added to 248 g of DI water and heated to 60° C. 19 g of 50 wt % sodium hydroxide solution was added to the zeolite suspension in water and the resulting mixture was stirred for 2 hours at 60° C. The desilicate zeolite was then filtered and washed with DI water.

[0040] Ammonium exchange of the desilicate zeolite was carried out using two contacts with ammonium nitrate solution (ammonium nitrate / zeolite weight ratio 2.5) at 80° C. for 2 hours. After each contact, the zeolite was filtered and washed with DI water. The ammonium exchanged sample was dried in air at 105° C. The ammonium exchanged sample exhibited the properties summarized in Table 1.

[0041] Example 5 100 g of as-synthesized OSDA-containing form of ZSM-5 zeolite with an average crystal size of 40 nm as shown in Table 1, SAR30, was added to 421 g of DI water mixed at room temperature. 71 g of 50 wt. % sodium hydroxide solution was added to the zeolite suspension in water and the resulting mixture was stirred at room temperature for 2 hours. The desilicate zeolite was then filtered and washed with DI water.

[0042] Acidified ammonium exchange of the desilicate zeolite was carried out at 80° C. for 2 hours using one contact with a mixed solution of nitric acid and ammonium nitrate (0.6:2.5:1 nitric acid:ammonium nitrate:zeolite weight ratio) and one with ammonium nitrate solution (2.5 ammonium nitrate / zeolite weight ratio). After each contact, the zeolite was filtered and washed with DI water. The ion-exchanged samples were dried at 105° C. in air. The ion-exchanged samples exhibited the properties summarized in Table 1.

[0043] Comparative Example 1 Comparative CBV 5524G zeolite, a commercial zeolite from Zeolyst International having an average crystal size of 230 nm as shown in Table 1, was treated under the same conditions as the inventive ZSM-5 of Example 1. 50 g of comparative ZSM-5 zeolite was added to 232 g of DI water and mixed at room temperature. 28 g of 50 wt % sodium hydroxide solution was added to the zeolite suspension in water and the resulting mixture was stirred at room temperature for 2 hours. The desilicate zeolite was then filtered and washed with DI water.

[0044] Ammonium exchange of the desilicate zeolite was carried out using two contacts with ammonium nitrate solution (ammonium nitrate / zeolite weight ratio 2.5) at 80° C. for 2 hours. After each contact, the zeolite was filtered and washed with DI water. The ammonium exchanged sample was dried in air at 105° C. The ammonium exchanged sample exhibited the properties summarized in Table 1.

[0045] Comparative Example 2 Comparative CBV 5524G zeolite, a commercial zeolite from Zeolyst International, was treated under the same conditions as the inventive ZSM-5 of Example 2. 50 g of comparative ZSM-5 zeolite was added to 223 g of DI water and mixed at room temperature. 37 g of 50 wt. % sodium hydroxide solution was added to the zeolite suspension in water and the resulting mixture was stirred at room temperature for 2 hours. The desilicate zeolite was then filtered and washed with DI water.

[0046] Ammonium exchange of the desilicate zeolite was carried out using two contacts with ammonium nitrate solution (ammonium nitrate / zeolite weight ratio 2.5) at 80° C. for 2 hours. After each contact, the zeolite was filtered and washed with DI water. The ammonium exchanged sample was dried in air at 105° C. The ammonium exchanged sample exhibited the properties summarized in Table 1.

[0047] Comparative Example 3 Comparative CBV 5524G zeolite, a commercial zeolite from Zeolyst International, was treated under the same conditions as the inventive ZSM-5 of Example 3. 50 g of comparative ZSM-5 zeolite was added to 251 g of DI water and heated to 40° C. 9.3 g of 50 wt % sodium hydroxide solution was added to the zeolite suspension in water and the resulting mixture was stirred at 40° C. for 2 hours. The desilicate zeolite was then filtered and washed with DI water.

[0048] Ammonium exchange of the desilicate zeolite was carried out using two contacts with ammonium nitrate solution (ammonium nitrate / zeolite weight ratio 2.5) at 80° C. for 2 hours. After each contact, the zeolite was filtered and washed with DI water. The ammonium exchanged sample was dried in air at 105° C. The ammonium exchanged sample exhibited the properties summarized in Table 1.

[0049] Comparative Example 4 Comparative CBV 5524G zeolite, a commercial zeolite from Zeolyst International, was treated under the same conditions as the inventive ZSM-5 of Example 4. 50 g of comparative ZSM-5 zeolite was added to 241 g of DI water and heated to 60° C. 19 g of 50 wt % sodium hydroxide solution was added to the zeolite suspension in water and the resulting mixture was stirred at 60° C. for 2 hours. The desilicate zeolite was then filtered and washed with DI water.

[0050] Ammonium exchange of the desilicate zeolite was carried out using two contacts with ammonium nitrate solution (ammonium nitrate / zeolite weight ratio 2.5) at 80° C. for 2 hours. After each contact, the zeolite was filtered and washed with DI water. The ammonium exchanged sample was dried in air at 105° C. The ammonium exchanged sample exhibited the properties summarized in Table 1.

[0051] Comparative Example 5 Comparative ZSM-5 with SAR25, a commercial CBV 2314 zeolite from Zeolyst International, was treated under the same conditions as the inventive ZSM-5 of Example 5. 100 g of comparative zeolite was added to 421 g of DI water mixed at room temperature. 71 g of 50 wt % sodium hydroxide solution was added to the zeolite suspension in water and the resulting mixture was stirred at room temperature for 2 hours. The desilicate zeolite was then filtered and washed with DI water.

[0052] Acidified ammonium exchange of the desilicate zeolite was carried out at 80°C for 2 hours using one contact with a mixed solution of nitric acid and ammonium nitrate solution (0.6:2.5:1 weight ratio of nitric acid:ammonium nitrate:zeolite) and one with ammonium nitrate solution (2.5 weight ratio of ammonium nitrate / zeolite). After each contact, the zeolite was filtered and washed with DI water. The ion-exchanged samples were dried at 105°C in air. The ion-exchanged samples exhibited the properties summarized in Table 1.

[0053] TIFF2025509589000001.tif153164

[0054] Alternative embodiments will be apparent to those skilled in the art from consideration of the specification and practice of the invention disclosed herein. It is intended that the specification and examples be considered as exemplary only, with the true scope of the disclosure being indicated by the following claims and equivalents thereof.

Claims

1. 1. A desilicate crystalline material having a MFI (ZSM-5) framework type, a silica to alumina molar ratio (SAR) of 15 or greater, and an average crystallite size of about 200 nm or less, said crystalline material having a crystallite size of at least 0.40 cm 3 / g and a mesopore volume of at least 0.10 cm 3 / g of micropore volume.

2. 2. The desilication crystalline material of claim 1, wherein the material has an average crystallite size of about 100 nm or less.

3. 3. A desilicate crystalline material according to claim 1 or 2, wherein said material has an average crystallite size in the range of 40 to 200 nm.

4. 4. A desilicate crystalline material according to any one of claims 1 to 3, wherein the material has an average crystallite size in the range of 50 to 100 nm.

5. 5. A desilication crystalline material according to any one of claims 1 to 4, wherein said material has a molar SAR in the range of 15 to 300.

6. 6. A desilicate crystalline material according to any one of claims 1 to 5, wherein said material contains an organic structure directing agent (OSDA) in an amount ranging from 0.1 to 10% by weight.

7. mixing a base material having an average crystal size of 200 nm or less in a base solution; recovering the solids by filtration or other separation method. drying, and Optionally, calcining the solid. A method for producing a desilication crystalline material according to any one of claims 1 to 6, comprising:

8. The base material is heated in a base solution containing 1 to 20 mmol of base per 1 g of anhydrous zeolite at a temperature range of 0° C. to 100° C. with a pressure of 0.40 cm 3 mixing for a time sufficient to form a mesopore volume of at least 1 / g; 8. The process according to claim 7, wherein the solids content, defined as the weight percentage of anhydrous zeolite relative to the total weight of the desilication slurry, is in the range of 1 to 40 wt.%.

9. The desilicate crystalline material is converted to NH by ion exchange with an ammonium salt or an acid. 4 9. The method according to claim 7 or 8, wherein the hydroxyl group is further processed to the H-form and the H-form.

10. 10. The method of claim 9, wherein the ammonium salt comprises ammonium nitrate or ammonium chloride.

11. 11. The method of claim 10 further comprising treating the desilicate crystalline material with an acid during ion exchange to promote dealumination of the desilicate mesoporous zeolite.

12. The method of claim 11 , wherein the acid comprises nitric acid or hydrochloric acid.

13. The method of any one of claims 7 to 12, wherein the host material does not include an OSDA.

14. The method of any one of claims 7 to 13, wherein the host material comprises an OSDA.

15. The method of any one of claims 7 to 14, wherein the matrix has a silica / alumina molar ratio in the range of 15 to 300.

16. The process according to any one of claims 7 to 15, wherein the base is selected from alkali metal hydroxides.

17. The base is LiOH, NaOH, KOH or NH 4 The method of any one of claims 7 to 16, further comprising OH.

18. The method according to any one of claims 7 to 17, wherein the base is selected from organic bases including tetraalkylammonium hydroxides.

19. 19. The method of any one of claims 7 to 18, wherein the desilicate crystalline material has a ΔV / silica loss ratio of at least 0.

8.

20. 20. The method of any one of claims 7 to 19, wherein the desilicate crystalline material has an average crystal size in the range of 40 to 200 nm.

21. 21. The method of claim 20, wherein the desilicate crystalline material has an average crystal size in the range of 50 to 100 nm.